A Three-Field Smoothed Formulation for Prediction of Large-Displacement Fluid-Structure Interaction via the Explicit Relaxed Interface Coupling (ERIC) Scheme (Communications in Computational Physics, 2018)
A three-field smoothed formulation is proposed in this paper for the resolutionof fluid-structure interaction (FSI) from the arbitrary Lagrangian–Eulerian perspective.The idea behind the proposed approach lies in different smoothing concepts.Both fluid and solid stress tensors are smoothly treated by the cell-based smoothed finite element method (CS-FEM) using four-node quadrilateral elements. In particular,the smoothed characteristic-based split technique is developed for the incompressibleflows whereas the geometrically nonlinear solid is settled through CS-FEM as usual.The deformable mesh, often represented by a pseudo-structural system, is furthertuned with the aid of a hybrid smoothing algorithm. The Explicit Relaxed InterfaceCoupling (ERIC) scheme is presented to interpret the nonlinear FSI effect, where allinteracting fields are explicitly coupled in alliance with interface relaxation methodfor numerical stability. The promising ERIC solver is in detail validated against thepreviously published data for a large-displacement FSI benchmark. The good agreementis revealed in computed results and well-known flow-induced phenomena areaccurately captured.